Iron uptake of etioplasts is independent from photosynthesis but applies the reduction-based strategy - Sági-Kazár, Máté; Sárvári, Éva; Cseh, Barnabás; Illés, Levente; May, Zoltán; Hegedűs, Csaba; Barócsi, Attila; Lenk, Sándor; Solymosi, Katalin; Solti, Ádám (Frontiers in Plant Science, 2023)
Iron (Fe) is one of the most important cofactors in the photosynthetic apparatus, and its uptake by chloroplasts have been also associated with the operation of the photosynthetic electron transport chain during reduction-based plastidial Fe uptake. Therefore, plastidial Fe uptake was considered not to be operational in the absence of the photosynthetic activity. Nevertheless, Fe is also required for enzymatic functions unrelated to photosynthesis, highlighting the importance of Fe acquisition by nonphotosynthetic plastids. Yet, it remains unclear how these plastids acquire Fe in the absence of photosynthetic function. Furthermore, plastids of etiolated tissues should already possess the ability to acquire Fe, since the biosynthesis of thylakoid membrane complexes requires a massive amount of readily available Fe. Thus, we aimed to investigate whether the reduction based plastidial Fe uptake solely relies on the functioning photosynthetic apparatus. We used Savoy cabbage plant as a model, which develops natural etiolation in the inner leaves of the heads due to the shading of the outer leaf layers. Foliar and plastidial Fe content of Savoy cabbage leaves decreased towards the inner leaf layers.The leaves of the innermost leaf layers proved to be etiolated, containing etioplasts which lacked the photosynthetic machinery and thus were photosynthetically inactive. However, we discovered that these etioplasts contained, and were able to take up Fe. Although, the relative transcript abundance of genes associated with plastidial Fe uptake and homeostasis decreased towards the inner leaf layers, both ferric chelate reductase FRO7 transcripts and activity was detected in the innermost leaf layer.Additionally, a significant NADP(H) pool and NAD(P)H dehydrogenase activity was detected in the etioplasts of the innermost leaf layer, indicating the presence of the reducing capacity that likely supports the reduction based Fe uptake of etioplasts. Based on these findings, the reduction based plastidial Fe acquisition should not be considered exclusively dependent on the photosynthetic functions.